Immunophenotyping of the cluster of differentiation 74, migration inhibitory factor, and cluster of differentiation 44 expression on human breast cancer-derived cell lines: CD74, MIF & CD44 immunophenotyping - Al Ssadh, Hussain; Al Abdulmonem, Waleed (International Journal of Health Sciences, 2019)
Objective: Cluster of differentiation (CD) 74, CD44, and macrophage migration inhibitory factor (MIF) are well known for their immunological functions; however, it has been shown that recently, CD74, CD44, and MIF have a role in tumor and tumor progression. This study was undertaken to investigate the expression of CD74, MIF, and CD44 in breast cancer cells. Materials and Methods: The expression of CD74, MIF, and CD44 molecules on the breast cancer-derived cell lines CAMA-1, 3,4-methylenedioxyamphetamine (MDA)-MB-231, and MDA-MB-43 was determined by flow cytometry, western immunoblotting, and confocal microscope. To validate the study the studying expression of CD74, MIF, and CD44 on the normal breast cell line 266LDM, whole cell lysate obtained from adult normal breast tissue and normal breast tissue. Results: The results show that all breast cancer cells overexpress CD74 isoforms, MIF, and CD44, in contrast to the normal cell lines and normal breast tissues, which express only CD44 and MIF in low levels. The expression of CD74, MIF, and CD44 was studied in the immortalized normal breast luminal cell line 226LDM, normal breast tissues, and lysate to validate the study. Conclusion: The data show, in this study, the evidence that breast cancer cell lines expressing three different isoforms of CD74. The results of the present study indicate a crucial role of CD74 in breast cancer cells along with MIF and CD44. The results also suggest that CAMA-1, MDA-MB-231, and MDA-MB-435 cells are poorly immunogenic, expressing low levels of HLA-A, B, and C and HLA-DR.